Information provided on the posting of workers. Part 1: the necessity of information. Part 2: a comparative analytical survey of websites set up by public administrations (Strasbourg, 2010)
" ... The purpose of this survey is not to present the state of transposition of the Posting Directive in different Member States, but to highlight the necessity of improving the quality of information provided to undertakings and workers. The effectiveness of the rule of law presupposes a proper understanding thereof by the stakeholders, both in the case of those required to apply these rules and the beneficiaries. Proper identification of the stakeholders for a better understanding of their respective needs is an essential factor in the delivery of adequate and better information. Yet, it appears today that the information is mainly directed towards foreign undertakings present on national territory in the framework of a temporary service offer in application of the Directive 96/71 on the posting of workers. It seldom concerns undertakings established on national territory who wish to temporarily post workers to another Member State or who want to use such a provision of services themselves. It is also rare that such information is directed towards the posted workers. ..."